A Systematic Review of Earthquake-Related Head Injuries. Issue Volume 34:Issue s1(2019) (May 2019) - Igarashi, Yutaka; Matsumoto, Narumi; Kubo, Tatsuhiko; Nakae, Ryuta; Yokobori, Shoji; Yokota, Hiroyuki
Abstract : Introduction: Earthquakes have killed around 800, 000 people globally in the past 20 years, with head injury being the main cause of mortality and morbidity. Aim: To conduct a systematic review to determine the characteristics of head injuries after earthquakes for better disaster preparedness and management. Methods: All publications related to head injuries and earthquakes were searched using Pubmed, Web of Science, the Cochrane Library, and Ichushi. Results: Thirty-six articles were included in the analysis. Head injury was the third most common cause of injury among survivors of earthquakes. The most common injury after an earthquake occurred was in the lower extremities (36.2%), followed by the upper extremities (19.9%), head (16.6%), spine (13.3%), chest (11.3%), and abdomen (3.8%). Earthquake-related head injuries were predominantly caused by a blunt strike (79%), and were more frequently associated with soft tissue injury compared to non-earthquake-related head injuries and less frequently with intracranial hemorrhage. The mean age of patients with earthquake-related head injuries was 32.6 years, and 55.1% of sufferers were male. The most common earthquake-related head injury was laceration or contusion (59.2%) while epidural hematoma was most common among inpatients with intracranial hemorrhage after an earthquake (9.5%). Early wound irrigation and debridement and antibiotics administration are needed to decrease the risk of infection. Mortality due to earthquake-related head injuries was 5.6%. Discussion: Head injury was the main cause of mortality and morbidity after an earthquake. The characteristics of earthquake-related head injuries differed from those of non-earthquake-related head injuries, including the frequency of multiple injuries, and occurrence of contaminated soft tissue injury and epidural hematoma. This knowledge is important for determining demands for neurosurgery and for adequate management of patients, especially in resource-limited conditions.